Effect of Mimosa pudica (mimosa)’s alcoholic extract on rat fertility - Arroyo, Jorge (2010)
Objectives: To determine whether oral administration of Mimosa pudica (mimosa) leaves ethanol extract modifies fertility in normal rats. Design: Experimental study. Setting: Instituto de Investigaciones Clinicas, Facultad de Medicina, Facultad de Farmacia, Universidad Nacional Mayor de San Marcos, Hospital Nacional Hipolito Unanue, Lima, Peru. Biological material: Albino rats and Mimosa pudica leaves. Methods: Forty-eight animals were divided randomly into groups of six animals each. The first was control and received saline solution 5 mL/kg and the others 50, 250 and 500 mg/kg oral extracts for 28 days. Each group considered 6 males and 6 females together. The animals were killed to observe the presence of fetuses in uterus. FSH, estradiol and progesterone levels were determined in μg /dL in female rats’ blood samples and hormone dosage was done by electrochemoluminiscence method. In the antiimplantation study 2 groups of 5 pregnant female rats were used; one group received water and the other 600 mg/kg plant extract doses for 10 days. Main outcome measures: Reduction in the number of fetuses and hormone levels. Results: Flavonoids, phenolics and tannins were in larger quantity in the ethanol extract. Rats that received 250 mg/kg showed a greater number of fetuses followed by 50 mg/kg, while 500 mg/kg dose decreased the number of fetuses as compared with rats not given the plant; FSH and progesterone showed increased levels. Conclusions: In experimental conditions Mimosa pudica’s 250 mg/kg doses increased fertility but 500 mg reduced fertility in normal rats.